Multimodal Literacy : The Use of Web Blog As Media of Teaching Writing At English Department of STKIP PGRI West Sumatera - Analido, Belinda; Pratiwi, Mia Audina (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This article reports on the investigation of the use of web blog as media in teaching writing to English Department Students of STKIP PGRI West Sumatera in Academic Year 2016 – 2017. It aims to research about the motivational factors for using blogs as an essential tool to promote students’ writing skills in EFL classrooms, specifically in English Department of STKIP PGRI West Sumatera. This study discusses how using blogs may be integrated into classroom activities to promote students’ writing skills as well as polishing their skills. It would also illustrate the features offered in blogs as well as the motivational essence that is attached to the blogs. To achieve the aim of the study. This includes the advantages and also the challenges of multimodal literacy in the implementation of using web blog as the medium of teaching writing. In addition, the data in this article were collected through semi-structured interviews by using a semin structured interview guide of protocol. The findings of the study would serve as an insistent reminder that the blogs which have been clearly underlined in the curriculum should be re-orchestrated more effectively again by the lecturers or teachers of English as a Foreign Language (EFL).